The cancer stem cell niche(s): The crosstalk between glioma stem cells and their microenvironment - Filatova, Alina; Acker, Till; Garvalov, Boyan K. (Biochimica et biophysica acta, 2013)
The initiation and progression of various types of tumors, including glioma, are driven by a population of cells with stem cell properties. Glioma stem cells (GSCs) are located in specialized microenvironments (niches) within tumors. These niches represent the hallmarks of malignant gliomas (vascular proliferations, hypoxia/necrosis) and bear analogy to the microenvironments in which physiological stem cells in the brain are found. Here we review the progress that has been made towards uncovering the function of the perivascular and the hypoxic niche and the molecular pathways that control the properties of GSCs within them. We propose models of how the different niches and GSC pools in them interact with each other. GSCs are not merely passive residents of their niches, but actively contribute to the shaping of the niches through a complex crosstalk with different components of the microenvironment. For example, GSCs play a dominant role in promoting new blood vessel formation through a variety of mechanisms, including the hypoxia dependent stimulation of angiogenesis, recruitment of endothelial progenitor cells and direct transdifferentiation into endothelial cells. Recent work has also revealed that GSCs can recruit and modulate the function of various immune cells to suppress anti-tumor immune responses and to foster tumor-promoting inflammation, which in turn could support the maintenance of GSCs. These findings underscore the central role of the GSC microenvironment in driving glioma progression making the GSC niche a prime therapeutic target for the design of therapies aimed at eradicating GSCs. This article is part of a Special Issue entitled Biochemistry of Stem Cells. ► Glioma stem cells (GSCs) are located in perivascular and hypoxic niches. ► GSCs and their niches intricately crosstalk, regulating each other's function. ► HIF-1α and HIF-2α are the key regulators of GSCs within the hypoxic niche. ► Notch signaling plays a key role within the perivascular niche. ► Niches are prime targets in tumor therapy as they maintain cancer stem cells.